Gender Bias in Malaysian English Language Textbooks Used in Secondary Schools - Chandran, Sanda Kumari (2002)
The purpose of this study was to identify occurrences of gender bias in four Form Four Malaysian English language textbooks. The study examined only the written text, looking at the occurrence of gender bias in the following categories: terms of address, descriptive terms, occupational of gender roles and activities, and the quantitative representation of male and female characters. The data indicates that the number of males portrayed in the textbooks far outweigh that of females. In addition, male characters were portrayed in a greater variety of occupations and as active participants in many outdoor activities, while female characters were largely portrayed in a limited number of occupations and roles and as participants in passive indoor activities. The findings also reveal that males are associated with more positive descriptive terms than women. Stereotyping is thus seen in the description of male and female characters in the textbooks, whether they were written by male or female writers. The study also looked at how teachers perceived and responded to the issue of gender bias in the textbooks. Data was collected by means of questionnaires. The response revealed that most teachers were unaware of gender bias in textbooks, their main concern being the completion of the syllabus according to the schedule. The findings of this study provide evidence of the occurrence of gender bias in Malaysian English language textbooks. This may prompt publishers, writers, TESL teachers, counsellors, administrators, curriculum planners, ESL learners and parents to be more aware of the phenomenon and to exercise greater caution in writing, reading, and teaching with textbooks. Further studies could be carried out to investigate how much or little attention publishers pay to the occurrence of gender bias in the books they publish, and whether textbooks evaluators include selection process.